PERMASALAHAN PENDIDIKAN DASAR DAN PENDIDIKAN ANAK USIA DINI - Hadi Siswanto (Center of Language and Cultural Studies, 2014)
A nine-year compulsory learning in Indonesia is a major program for all children. However, several problems seem to be unsolved as the focus of the is bias. This paper describes the role of basic education and its drawbacks. The limitation arises from management and restricts conditions where teachers and facilities are in trivialities. Basic education in Indonesia is now developing and three kinds of institution exist at present: Elementary School, Islamic School, and Boarding School. The institutions are basic model of Indonesian elementary school, but they receive different treatments.